The Role of Entrepreneurship Education on Internationalization Intention. A Case Study from Izmir-TURKEY - Yarkin, Dinçer; Yeliz YEŞİL (European Journal of Social Science Education and Research, 2016)
Acting in a domestic market can be risky for new ventures in developing countries because of vulnerable economic and politic conditions. From the beginning of establishment, focusing on international markets can prevent local market risks which new entrepreneurs will probably encounter. Internationalization, entrepreneurship and international entrepreneurship are the main topics which scholars given more attention in the world. In this study, entrepreneurship education and it’s effects on generating internationalization intention were evaluated by in depth interviews. Findings has shown that type of the institute, course content, classmates, qualification and background of the lecturer, plays important role on initiation of starting international business
Keywords: Entrepreneurship, Entrepreneurial Intention, Entrepreneurship Education, Internationalization.